2004
DOI: 10.1212/01.wnl.0000130181.05016.68
|View full text |Cite
|
Sign up to set email alerts
|

Reversible hyperintensity lesion on diffusion-weighted MRI in hypoglycemic coma

Abstract: In a woman aged 73 years who recovered from hypoglycemic coma without neurologic deficit after glucose infusion, admission diffusion-weighted MRI showed the presence of hyperintensive lesions. The lesions regressed after glucose infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
74
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 10 publications
3
74
1
4
Order By: Relevance
“…[1][2][3] Neuropathologic studies have demonstrated that the cerebral cortex, hippocampus, and BG are commonly affected sites in severe hypoglycemia; however, the cerebellum and brain stem are usually spared. [4][5][6][7][8][9][10] In addition, unlike hypoxic damage, the occipital cortex, dorsofrontal cortex, and hippocampus may be more resistant to prolonged hypoglycemia. 9 Some studies have described MR imaging of hypoglycemic brain injury, though these studies have usually been confined to case reports; in most of the reported studies, DWI is useful in evaluating severe HE.…”
mentioning
confidence: 99%
“…[1][2][3] Neuropathologic studies have demonstrated that the cerebral cortex, hippocampus, and BG are commonly affected sites in severe hypoglycemia; however, the cerebellum and brain stem are usually spared. [4][5][6][7][8][9][10] In addition, unlike hypoxic damage, the occipital cortex, dorsofrontal cortex, and hippocampus may be more resistant to prolonged hypoglycemia. 9 Some studies have described MR imaging of hypoglycemic brain injury, though these studies have usually been confined to case reports; in most of the reported studies, DWI is useful in evaluating severe HE.…”
mentioning
confidence: 99%
“…Aoki et al described reversible abnormalities in diffusionweighted MRI 10 days after glucose infusion 9 . In fact, as the reversible brain-imaging abnormalities and hemiparesis caused by hypoglycemia can mimic a transient ischemic attack or stroke 10 , the determination of blood glucose levels, the effects of its infusion and the comparison of MRI images on the day of admission to one taken several days after glucose infusion can be useful tools to make differential diagnosis 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Another considerable hypothesis is the disruption of protein synthesis in the superficial layers of the cortex, in the basal ganglia, and hippocampus 1,9 . On the other hand, the cerebellum and brain stem are less affected by this mechanism because they have effective strategies to transport glucose 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations